Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.virol.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Binding of host factors to stabilized HIV-1 capsid tubes

Abstract: The capsid-binding assay is an in vitro experiment used to determine whether cellular proteins interact with the HIV-1 core. In vitro assembled HIV-1 capsids recapitulate the surface of the HIV-1 core. The assay involves the incubation of in vitro assembled HIV-1 capsid-nucleocapsid (CA-NC) complexes with the protein in question. Subsequently, the mixture is spun through a sucrose cushion using an ultracentrifuge, and the pellet is analyzed for the presence of the protein in question. Although this binding ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…The appearance of the capsid tubes as lines in the fluorescence image facilitates detection and extraction of traces using automated image analysis. Tubular CA lattices are commonly used in binding studies as surrogates for the capsid 16,18,38,39 but lack CA pentamers and the variable curvature of the native conical capsid. Combining our biosensor as a tool for routine measurements with more specialised approaches using virus-like particles 32 should overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the capsid tubes as lines in the fluorescence image facilitates detection and extraction of traces using automated image analysis. Tubular CA lattices are commonly used in binding studies as surrogates for the capsid 16,18,38,39 but lack CA pentamers and the variable curvature of the native conical capsid. Combining our biosensor as a tool for routine measurements with more specialised approaches using virus-like particles 32 should overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…We used self-assembly of recombinant CA A14C/E45C at high salt concentrations to produce tubular lattices of disulfide cross-linked CA hexamers 26 as biorecognition elements representing the HIV-1 capsid. 18 These stabilised tubes were rendered fluorescent by coassembly with a small fraction of CA K158C reacted with a fluorophore at the engineered cysteine (Supplementary Figure S1 and S2). This co-assembly reaction also yielded long tubes that aggregated into bundles in solution ( Figure 2A), a process known to be driven by interactions between hydrophobic residues (primarily located in the CypA loop of CA) on the outer tube surfaces.…”
Section: Growth Of Fluorescent Capsid Tubes On the Sensor Surface As mentioning
confidence: 99%
“…Experiments using our nuclear import functional assay suggested that assembled capsids are transported into the nucleus; however, the western blots cannot distinguish between assembled or disassembled capsid within the nucleus. To directly test whether large assembled capsid complexes can be imported into the nucleus using an HIV-1 core resistant to disassembly, we produced an HIV-1 virus with a stabilized capsid, taking advantage of the capsid mutations A14C/E45C that stabilize purified capsid hexamers in vitro through disulfide bridges between monomers of hexamers (Pornillos et al, 2010;Selyutina et al, 2018). This virus lacked defects in viral budding, maturation, and reverse transcription; however, HIV-1-A14C/E45C virus was incapable of forming 2-LTR circles and productive infection ( Figure S4).…”
Section: Hiv-1 Infectionmentioning
confidence: 99%
“…If TRIM5α hu restriction occurs after cells are infected by HIV-1-N74D, it implies that Cyp A is no longer protecting the core. To test this hypothesis, we assessed the abilities of TRIM5α hu and Cyp A to bind to N74D-stabilized capsid tubes using a capsid binding assay [13]. As shown in Figure 5, TRIM5α hu bound with increased affinity to stabilized N74D capsid tubes than to wild-type tubes.…”
Section: Resultsmentioning
confidence: 99%